Outcomes of Mechanically Ventilated Liver Failure Patients Admitted to the Intensive Care Unit. Issue 6 (November 2016) - Sta Cruz, Joanna Paula; Punjabi, Chitra; Lippmann, Michael
Abstract : Background: Aggressive treatment of mechanically ventilated liver failure patients has been questioned as they frequently succumb to multiorgan failure. However, survivors have a chance at liver transplantation, and the knowledge of mortality predictors may help decrease the wait-list mortality. We aimed to determine outcomes of this population and determine which variables predict mortality. Materials and Methods: A retrospective study of 131 mechanically ventilated liver failure patients admitted to the intensive care unit (ICU) of a major liver transplant center from January 2011 to June 2014 with a follow-up period of 1 year. Results: The most common indication for ICU admission and intubation was hepatic encephalopathy. The median length of intubation was 4 days. Patients intubated for miscellaneous reasons spent the longest time on mechanical ventilation at a median of 12 days followed by sepsis and respiratory failure. In-hospital and 1-year mortalities were 54% and 71%, respectively. Only 5 of 27 patients listed for transplant received an organ. Patients readmitted to the ICU were 4 times more likely to die in 1 year. A Model for End Stage Liver Disease (MELD) score >40 and chronic kidney disease were the strongest predictors for overall mortality. A MELD score >40 was the sole predictor for in-hospital mortality. Acute renal failure, ICU readmission, and hepatic encephalopathy were additional predictors for postdischarge mortality. Conclusions: The in-hospital mortality remains as high at 54%. The MELD score was consistently a predictor for overall, in-hospital, and postdischarge mortalities. Patients readmitted to the ICU were 4 times more likely to die in 1 year. Most survivors who were liver transplant candidates died waiting for an organ.